Effects of Formaldehyde Fumigation and Fytolan Drench on VAM fungi and nodulation in some Leguminous forest Tree Seedlings in India - Udaiyan, K.; Sugavanam, V.; Manian, S. (Universiti Putra Malaysia Press, 1996)
Seedlings of 12 legume tree species (Acacia caesia, A. catechu, A. farnesiana, A. holosericea, A. leucocephala, A. nilotica, Albizia lebbeck, Dichrostachys cinerea, Leucaena latisiliqua, Prosopis cineraria, Dalbergia latifolia and Pterocarpus marsupium) were raised informaldehyde-fumigatedf Fytol and renched beds in a nursery. Seedlings in the formaldehyde fumigated beds had stunted growth and were chlorotic; had poor VAM root colonization (18-25.3%) and spore density (3.1 - 10.6 g. soil-1 ) and lower nodule number (3 - 8 plant-1 ) and nodular biomass (100 - 870 mg plant-1 ); the total biomass (15.5 - 72 g plant-1 ) and field survival rate (31.2 - 40.4%) of the seedlings were very low. The mycorrhizal species isolated were Acaulospora bireticulata, Glomus fasciculatum and G. geosporum. In contrast, seedlings form Fytolan-drenched beds showed normal growth, enhanced biomass (18 - 83.21g plant-1 ) and higher field survival rate (71 - 86%); intense VAM root colonization (53.4-100%) and higher spore density (36 - 82.8 g soil-1 ) and higher module number (7.4 - 17.6 plant-1 ) and nodular biomass (195 - 950 mg plant ) compared with the control seedlings. Roots of these plants exhibited extensively developed arbuscular and vesicular structures. Ofthe seven VAMF species recordedfrom the rhizosphere soils of control and Fytolan-drenched beds, A. bireticulata, G. fasciculatum and G. geosporum were the dominant species. The differences between treatments were statistically significant (P < 0.05).